Gerenciamento do alto índice de rotatividade de mão de obra na manufatura: um estudo de caso - Netto, Amanda Silva (Universidade do Vale do Rio dos Sinos, 2024)
Labor turnover has become a topic of growing interest among researchers worldwide. When not properly managed, turnover can generate significant negative impacts, such as increased costs associated with dismissal, hiring, and training, as well as affect the productivity and quality of the products or services offered by the company. In light of this, it is essential to study this phenomenon in depth to better understand it and propose effective solutions for its management. The present study aims to analyze the internal and external causes that contribute to voluntary employee turnover in the manufacturing sector, with the goal of offering suggestions to address the problem. The case study employs a work method that analyzes data categorized as past, present, and future to gain a thorough understanding of turnover behavior over time, enabling the creation of strategies to minimize the problem. The results indicate that understanding the organizational context is essential for creating effective strategies. Based on this analysis, it was possible to propose approaches that are better aligned with the company's needs, increasing the chances of success in talent retention.
Keywords: Rotatividade mão de obra; Impactos da rotatividade; Causas de rotatividade; Retenção de funcionários; Labor turnover; Impacts of turnover; Causes of turnover; Employee retention; ACCNPQ::Engenharias::Engenharia de Produção